2020
DOI: 10.1021/acs.est.0c04674
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Metal Ions on Oxidation of Micropollutants by Ferrate(VI): Enhancing Role of FeIV Species

Abstract: This paper investigated the oxidation of recalcitrant micropollutants [i.e., atenolol (ATL), flumequine, aspartame, and diatrizoic acid] by combining ferrate(VI) (Fe VI O 4 2− , Fe VI ) with a series of metal ions [i.e., Fe(III), Ca(II), Al(III), Sc(III), Co(II), and Ni(II )]. An addition of Fe(III) to Fe VI enhanced the oxidation of micropollutants compared solely to Fe VI . The enhanced oxidation of studied micropollutants increased with increasing [Fe(III)]/[Fe VI ] to 2.0. The complete conversion of phenyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
62
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 95 publications
(82 citation statements)
references
References 73 publications
4
62
0
Order By: Relevance
“…In the aforementioned discussion, the UVA-LED/Fe­(VI) process could remarkably promote SMX degradation. During this process, the possible decomposition products of Fe­(VI) (e.g., Fe­(III) and H 2 O 2 ) participated in the micropollutant degradation. , Recent findings showed that the newly added Fe­(III) from the FeCl 3 solution played a catalytic role in the Fe­(VI) oxidation of micropollutants . The role of Fe­(III) was explored by adding Fe­(III) that was prepared via the Fe­(VI) decay under UVA-LED irradiation after 30 min into the reaction.…”
Section: Resultsmentioning
confidence: 99%
“…In the aforementioned discussion, the UVA-LED/Fe­(VI) process could remarkably promote SMX degradation. During this process, the possible decomposition products of Fe­(VI) (e.g., Fe­(III) and H 2 O 2 ) participated in the micropollutant degradation. , Recent findings showed that the newly added Fe­(III) from the FeCl 3 solution played a catalytic role in the Fe­(VI) oxidation of micropollutants . The role of Fe­(III) was explored by adding Fe­(III) that was prepared via the Fe­(VI) decay under UVA-LED irradiation after 30 min into the reaction.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the oxidation of amines will eliminate one of the precursors in water that generate DBPs during chlorination; ,, therefore, the amount of chlorinated DBPs would decrease in the use of Fe­(VI) as a preoxidant before chlorination. Fe­(VI) has been demonstrated to be an effective disinfectant and coagulant. , Therefore, application of Fe­(VI) has a potential to have multiple advantages in treatment processes.…”
Section: Discussionmentioning
confidence: 99%
“…24,26 The Fe IV /Fe V species are present at low steady-state concentrations and only for time scales in the range from microseconds to milliseconds. 30,32,33 approaches to identify Fe IV /Fe V species in an aqueous environment were not successful. 30,32 The demonstration of the intermediate Fe IV /Fe V species is restricted to a nonaqueous (or organic) solvent in which the central iron is complexed by bulky organic ligands such as porphyrins and 1,4,8,11-tetramethyl-1,4,8,11-tetraazacyclotetradecane.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings have profound implication in Fe­(VI) technologies for mitigation of EOCs in water and wastewater industries. Given that Fe­(V) and Fe­(IV) are much more reactive than Fe­(VI), ,, the generation of more Fe­(V) and Fe­(IV) from Fe­(VI) is one of the promising approaches for more efficient destruction of EOCs in Fe­(VI) applications. If the in situ production of Fe­(V) and Fe­(IV) can be well harnessed, better EOCs removals and lower Fe­(VI) dosages are expected in practices for improving the efficiency of Fe­(VI) treatment and saving the operation costs associated with water treatment.…”
Section: Environmental Implicationsmentioning
confidence: 99%